Boosting Selective Oxidation of Ethylene to Ethylene Glycol Assisted by In situ Generated H2O2 from O2 Electroreduction - Guan, Ming‐Hao; Dong, Ling‐Yu; Wu, Tao; Li, Wen‐Cui; Hao, Guang‐Ping; Lu, An‐Hui (Angewandte Chemie International Edition, 2023)
Ethylene glycol is a useful organic compound and chemical intermediate for manufacturing various commodity chemicals of industrial importance. Nevertheless, the production of ethylene glycol in a green and safe manner is still a long‐standing challenge. Here, we established an integrated, efficient pathway for oxidizing ethylene into ethylene glycol. Mesoporous carbon catalyst produces H2O2, and titanium silicalite‐1 catalyst would subsequently oxidize ethylene into ethylene glycol with the in situ generated H2O2. This tandem route presents a remarkable activity, i.e., 86 % H2O2 conversion with 99 % ethylene glycol selectivity and 51.48 mmol gecat−1 h−1 production rate at 0.4 V vs. reversible hydrogen electrode. Apart from generated H2O2 as an oxidant, there exists ⋅OOH intermediate which could omit the step of absorbing and dissociating H2O2 over titanium silicalite‐1, showing faster reaction kinetics compared to the ex situ one. This work not only provides a new idea for yielding ethylene glycol but also demonstrates the superior of in situ generated H2O2 in tandem route. The in situ generated H2O2 from O2 electroreduction over mesoporous carbon is applied to oxidize ethylene via titanium silicalite‐1. The in situ generated ⋅OOH on the mesoporous carbon can form the key active species Ti‐OOH over titanium silicalite‐1 and oxidize ethylene. This route exhibits outstanding production rate and selectivity of ethylene glycol.